2015
DOI: 10.1007/s12665-015-4295-9
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent C, N and P stoichiometry of three submersed macrophytes along water depth gradients

Abstract: Variability in biomass allocation and growth rate of submersed macrophytes along water depth gradients may lead to different carbon (C), nitrogen (N) and phosphorus (P) stoichiometric characteristics. We conducted a field investigation to evaluate long-term effects of water depth on C, N and P stoichiometry of three submersed macrophytes, Potamogeton maackianus, Myriophyllum spicatum and Ceratophyllum demersum. The results indicated that shoot C:N, C:P and N:P of the plants tended to increase with elevated wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…The leaf P concentration and the C:P and N:P mass ratios in A. sparsifolia were significantly affected by groundwater depths in both years ( Figure 3 ). This results is similar to previous findings, indicating that the leaf P concentrations and C:P and N:P mass ratios of the submersed macrophytes are affected by increasing groundwater depths ( Li W. et al, 2015 ). The effect of groundwater depth on leaf P concentration is likely attributed to soil and groundwater that serve as the only sources of P absorbed by A. sparsifolia in the current study; thus this phenomenon can be significantly affected by external environments ( Hedin, 2004 ; Rong et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The leaf P concentration and the C:P and N:P mass ratios in A. sparsifolia were significantly affected by groundwater depths in both years ( Figure 3 ). This results is similar to previous findings, indicating that the leaf P concentrations and C:P and N:P mass ratios of the submersed macrophytes are affected by increasing groundwater depths ( Li W. et al, 2015 ). The effect of groundwater depth on leaf P concentration is likely attributed to soil and groundwater that serve as the only sources of P absorbed by A. sparsifolia in the current study; thus this phenomenon can be significantly affected by external environments ( Hedin, 2004 ; Rong et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
“…Many studies on ecological stoichiometry have been conducted in the presence of different environmental factors, such as nutrients, light, prescribed burning, and plantation age ( Herbert et al, 2003 ; Striebel et al, 2008 ; Xing et al, 2013 ; Butler et al, 2017 ; Zeng et al, 2017 ). Li W. et al (2013) and Li W. et al (2015) also found that water depth gradients remarkable affected the C, N, and P concentrations and mass ratios of macrophytes in Lake Erhai.…”
Section: Introductionmentioning
confidence: 91%
“…In water column, our study showed that water depth has a significant negative effect on plant tissue P which is Fig. 3 Variance partitioning based on pRDA analysis for sediment, water column, and taxonomy on tissue C:N:P stoichiometric signatures Table 6 Percentage (100 %) of explained variance based on variance partitioning for C:N:P stoichiometric signatures and for C, N, P, C:N, C:P, and N:P, respectively, in response to sediment, water column, and taxonomy The p values which <0.001 were emphasized in boldface S sediment, W water column, T taxonomy consistent with previous study (Li et al 2015). Indeed, in deep water, most submerged macrophytes tend to allocate more biomass to stem for shoot elongation to alleviate low light availability (Fu et al 2012;Strand and Weisner 2001).…”
Section: Sources Of Variability In Aquatic Plant Tissue Stoichiometrysupporting
confidence: 84%
“…3 ) as a carbon source (Lepoint et al, 2004). Leaf C:N ratios were largely affected by species identity, which is accordant to findings by Li et al (2015) that species differences in the allocation of nutrients are likely to be more important for the variability of C:N rather than growth rates of aquatic plants. The marginally non-significant relationship between leaf tissue C:N and productivity indicated that there could have been an underlying role for relative species abundances to affect productivity.…”
Section: Increased Productivity Had Carbon Consequencessupporting
confidence: 78%